Analysis of the results of problem solution during mathematics olympiads for fifth grade students - Piaseckienė, Karolina (Lietuvos matematikos rinkinys, 2018)
The article deals with the analysis of the results of problem solution during the mathematics olympiads of fifth grade students (stage 2) held in Šiauliai city in 2015–2018.